2011
DOI: 10.1111/j.1582-4934.2011.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced internalization of ErbB2 in SK-BR-3 cells with multivalent forms of an artificial ligand

Abstract: Targeting and down-regulation of ErbB2, a member of EGF receptor family, is regarded as one of the key aspect for cancer treatment because it is often overexpressed in breast and ovarian cancer cells. Although natural ligands for ErbB2 have not been found, unlike other ErbB receptors, EC-1, a 20-amino acid circular peptide, has been shown to bind to ErbB2 as an artificial ligand. Previously we showed EC-1 peptide did not induce the internalization of ErbB2 in SK-BR-3 cells. In this report, we designed divalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…It has been reported that SKBR-3 cells internalize their overexpressed ErbB2 receptors in a clathrin- and caveolin- independent endocytic pathway45. What is more, SKBR-3 cells lack caveolae, and ErbB2 internalization is sensitive to the depletion of cholesterol, which is necessary for most of the clathrin-independent pathways46. In addition, an association between macropinocytosis and tumor progression/metastasis has been reported47.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SKBR-3 cells internalize their overexpressed ErbB2 receptors in a clathrin- and caveolin- independent endocytic pathway45. What is more, SKBR-3 cells lack caveolae, and ErbB2 internalization is sensitive to the depletion of cholesterol, which is necessary for most of the clathrin-independent pathways46. In addition, an association between macropinocytosis and tumor progression/metastasis has been reported47.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence indicates that overexpressed ErbB2 traffics through the endocytic recycling pathway (15)(16)(17)(18). As endocytic recycling of ErbB2 is thought to critically contribute to its oncogenic signaling (18,80), and enhanced lysosomal degradation of ErbB2 is seen with ErbB2-targeted therapeutics (10,78), a better understanding of the biochemical pathways that regulate ErbB2 recycling is of substantial interest.…”
Section: Resultsmentioning
confidence: 99%
“…An important determinant of the oncogenicity of ErbB2 is its propensity to avoid lysosomal degradation and to instead traffic via the endocytic recycling pathway (15)(16)(17)(18). Molecular pathways that regulate ErbB2 recycling however remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further the establishment of the model system will be advantageous for the replenishment of CSC, as in long turn in vitro culture system these cells undergo differentiation to normal cancer cells. Enrichment of CD44 expressing cells would be a better platform in the drug targeting experiments for CSCs as we previously successfully showed targeting HER2 breast cancer cells with our bionanocapsule [37] and liposome [38,39] with HER2-binding artificial ligands and such models will provide extensive knowledge in the therapeutic intervention in curbing the cancer growth and metastasis. The advantage of our model involves its cost-effective enrichment of the CD44 expressing glioblastoma cells cells were the up regulation were found to be 2-fold when compared with adherent HA-conditions.…”
Section: Resultsmentioning
confidence: 99%